That time I got reincarnated as a slime. 14 - Fuse (Manga author); Kawakami, Taiki (Kodansha Comics, 2020)
"The hostile human nation of Falmuth staged a devastating attack on Tempest, the peaceful land of monsters. Now, in order to bring back the dead and protect the living, Rimuru is determined to become the most feared of beings: a Demon Lord. But this evolution comes at a terrible price, and the assailing humans will soon realize how poorly they've chosen their enemy..."--Provided by publisher.